Epidural analgesia for coronary artery bypass graft surgery - Riedel, Bernard J C J (Department of Anaesthesia, 2017)
On reviewing the medical literature, there is a clear resurgence of interest in the use of TEA (thoracic epidural analgesic) in cardiac anaesthesia. This resurgence was brought about by laboratory-based evidence that TEA-induced sympatholysis may be cardioprotective through the promotion of myocardial blood flow to areas at-risk and subsequent early, small clinical studies suggesting that TEA was feasible, and possibly also beneficial in CABG surgery [Joachimsson et. al, 1989; Liem (1-3) et. al, 1992; Stenseth et. al, 1994]. Despite the positive results of these early studies and suggestions that TEA may be the preferred anaesthetic/analgesic technique in select groups of patients (promoting early extubation and fast-tracking) undergoing cardiac surgery, many anaesthetists are still reluctant, however, to use this technique because of the theoretical increased risk of the patient suffering a spinal haematoma and subsequent paraplegia. In order to outweigh this theoretical risk it is important that we show that added benefit, in addition to the provision of analgesia and expedited postoperative convalescence, can be obtained by using TEA. It is therefore our duty as anaesthetists and perioperative physicians to determine whether TEA may also affect the pathophysiology of the disease process, especially in the perioperative period - and thereby influencing the subsequent long term outcome and quality of life of the patient. An example of this latter point would be the potential role of TEA in; • reducing the incidence of perioperative myocardial infarction (P-MI), through the suggested cardioprotective effects of TEA, • reducing the incidence of early postoperative graft failure, through either; * reduction of native coronary artery and/or graft (conduit) spasm, or * reduction of postoperative hypercoagulability.